Increased expression of PD-L1 in endometrial cancer stem-like cells is regulated by hypoxia - Shasha Yin; Yu’e Guo; Xinyue Wen; Hongliang Zeng; Guofang Chen (Frontiers in Bioscience-Landmark, 2022)
Background: The expression levels of the programmed cell death ligand 1 (PD-L1), known as an immune-inhibitory molecule, are closely associated with cancer stem cell (CSCs) immune escape. Recently, PD-L1 has also been reported to be able to regulate the self-renewal of cancer stem cells. However, The expression and intrinsic role of PD-L1 in endometrial cancer stem-like cell (ECSC) maintenance and its underlying mechanism of action remain unclear. Methods: Using flow cytometry and western blot assays, we have demonstrated that PD-L1 expression is higher in ECSCs derived from endometrial cancer than in nonstem-like cancer cells. Using mouse xenograft assays for ECSC tumorigenicity. Using gene reporter assay for uncovering the regulation mechanism of PD-L1 in the hypoxia. Results: We revealed the high expression levels of PD-L1 in ECSCs and its correlation with self-renewal. We further found that PD-L1 knockdown reduced expression of several pluripotency-related genes (aldehyde dehydrogenase 1 (ALDH1), CD133, OCT4, SOX2, NANOG), impaired ECSC proliferation and undifferentiated colonies and decreased the number of CD133 positive ECSCs and the number of stem-like spheres. Furthermore, we found that PD-L1 knockdown inhibited ECSC tumorigenicity and the PD-L1 induced self-renewal capability of ECSCs was dependent upon hypoxia HIF-1α and HIF-2α activation. Conclusions: These data link ECSC maintenance to PD-L1 expression through hypoxia and suggest a promising target for PD1/PD-L1 immunotherapy.